2013
DOI: 10.1098/rspb.2013.0176
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic variation of heritability and maternal effects in yellow-bellied marmot alarm calls

Abstract: Individuals of many species produce distinctive vocalizations that may relay potential information about the signaller. The alarm calls of some species have been reported to be individually specific, and this distinctiveness may allow individuals to access the reliability or kinship of callers. While not much is known generally about the heritability of mammalian vocalizations, if alarm calls were individually distinctive to permit kinship assessment, then call structure should be heritable. Here, we show conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Similarly to previous studies (RĂ©ale et al ., ; Taylor et al ., ), we found that permanent environment effects are present for these traits suggesting that the consistent environment potentially plays an equally important role in accounting for phenotypic variation as the underlying genes (see also Blumstein et al ., ). Female marmots are philopatric (Armitage, ) and experience the same environment throughout life.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly to previous studies (RĂ©ale et al ., ; Taylor et al ., ), we found that permanent environment effects are present for these traits suggesting that the consistent environment potentially plays an equally important role in accounting for phenotypic variation as the underlying genes (see also Blumstein et al ., ). Female marmots are philopatric (Armitage, ) and experience the same environment throughout life.…”
Section: Discussionmentioning
confidence: 97%
“…Acoustic characteristics such as fundamental frequency and sound amplitude, have different effects on parental care ( Lingle et al, 2012 ), and we therefore expect that these characteristics have different heritabilities ( Gustafsson, 1986 ; Price and Schluter, 1991 ; Branchi et al, 2001 ; Thornton et al, 2005 ). A low heritability usually indicates intense neutralizing selection, whereas high heritabilities are often associated with phenotypes that either do not greatly affect fitness (relaxed selection) or that are controlled by balancing selection ( Walsh and Lynch, 2018 ) that increases variability, perhaps in order to enhance kin and litter recognition ( Forstmeier et al, 2009 ; Blumstein et al, 2013 ). Hahn et al (1997) hypothesized that rates of calling has undergone more intense selection than other characters ( Hahn et al, 1997 ), however Spence et al (2016) have shown that acoustic characteristics usually do not change in isolation but are highly interrelated ( Spence et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, much of the attention that has been given to investigating matrilineal signatures in mammalian vocalizations has focused on social species (ie. goats [ 8 , 9 ], meerkats [ 10 ], marmots [ 11 ], sperm whales and killer whales [ 12 - 14 ], bats [ 15 - 17 ] and the socially variable house mouse [ 18 , 19 ]). Much less has been done on solitary species (i.e., pandas [ 20 ]).…”
Section: Introductionmentioning
confidence: 99%